Analisis Penggunaan Umpan pada Jaring Insang (Gillnet) - mustasim mustasim; Abudarda Razak; Muhfizar Muhfizar (Jurnal Airaha, 2013)
The research aimed to determine difference in gillnet catches baited and unbaited. The research was conducted in the waters of Sorong, Raja Ampat and Katapop Pantai, Kabupaten Sorong in November 2012 – January 2013 by using a gillnet pieces baited and 1 pieces gillnet without bait. The type both of them gillnet is operated together. The use of bait on gillnet did not significantly affect the number of catches. Number of gillnet catches barted in this study were 178 fish (49.03%) and gillnet unbaited is 183 fish (50.97%). Overall, the catch is dominated by Queen fish (Chrorinemus spp) fish there are 146 fish or 40.67 from of the total catch. Result catches between gillnet with baited and without bait. Gillnet that uses bait consisting of 15 species of which 2 types of gillnet catches there were not baited the Shark (Charcarias sp) and Crab (Scylla setata). While not baited gillnet consists of 14 species in which there is one species is not obtained at the baited gillnet that is Canine catfish eet (Plotosus canius).